Humanitarianism: Keywords - De Lauri, Antonio (Brill, 2020)
Humanitarianism: Keywords is a comprehensive dictionary designed as a compass for navigating the conceptual universe of humanitarianism. It is an intuitive toolkit to map contemporary humanitarianism and to explore its current and future articulations. The dictionary serves a broad readership of practitioners, students, and researchers by providing informed access to the extensive humanitarian vocabulary. Readership: Students and researchers of humanitarian studies, and all interested in post-war and post-disaster relief, emergency, crisis, and international interventions. Also of interest for practitioners and workers of NGOs and humanitarian organizations.